Heterochromatin in the fungal plant pathogen, Zymoseptoria tritici: Control of transposable elements, genome plasticity and virulence - Fraser, Callum J.; Whitehall, Simon K. (Frontiers in Genetics, 2022)
Heterochromatin is a repressive chromatin state that plays key roles in the functional organisation of eukaryotic genomes. In fungal plant pathogens, effector genes that are required for host colonization tend to be associated with heterochromatic regions of the genome that are enriched with transposable elements. It has been proposed that the heterochromatin environment silences effector genes in the absence of host and dynamic chromatin remodelling facilitates their expression during infection. Here we discuss this model in the context of the key wheat pathogen, Zymoseptoria tritici. We cover progress in understanding the deposition and recognition of heterochromatic histone post translational modifications in Z. tritici and the role that heterochromatin plays in control of genome plasticity and virulence.